4D printing roadmap - Bodaghi, Mahdi; Wang, Linlin; Zhang, Fenghua; Liu, Yanju; Leng, Jinsong; Xing, Ruizhe; Dickey, Michael D; Vanaei, Saeedeh; Elahinia, Mohammad; Hoa, Suong Van; Zhang, Danchen; Winands, Katarina; et al. (Smart materials and structures, 2024)
Four-dimensional (4D) printing is an advanced manufacturing technology that has rapidly emerged as a transformative tool with the capacity to reshape various research domains and industries. Distinguished by its integration of time as a dimension, 4D printing allows objects to dynamically respond to external stimuli, setting it apart from conventional 3D printing. This roadmap has been devised, by contributions of 44 active researchers in this field from 32 affiliations world-wide, to navigate the swiftly evolving landscape of 4D printing, consolidating recent advancements and making them accessible to experts across diverse fields, ranging from biomedicine to aerospace, textiles to electronics. The roadmap’s goal is to empower both experts and enthusiasts, facilitating the exploitation of 4D printing’s transformative potential to create intelligent, adaptive objects that are not only feasible but readily attainable. By addressing current and future challenges and proposing advancements in science and technology, it sets the stage for revolutionary progress in numerous industries, positioning 4D printing as a transformative tool for the future.
Gesehen am 29.07.2025